Analisis Pembentukan Personal Branding Anwar Hafid Melalui Facebook Menghadapi Pilgub Sulawesi Tengah 2024 - Caisaria, Rachmat; Sari, Yunita; Handayani, Mediana (Universitas Prof. Dr. Moestopo (Beragama), 2023)
This research aims to analyze the strategy and concept of forming Anwar Hafid's personal branding for the 2024 Central Sulawesi gubernatorial election. This research uses a qualitative approach with qualitative content analysis (QCA) techniques as a tool for collecting any data in the form of posts on Anwar Hafid's Facebook page, both photos and videos, which is then linked to personal branding theories. Data collection uses two techniques, namely observation and documentation, and four stages of analysis, namely data collection, data reduction, presentation, and verification/conclusion. The results of this research show that the strategy used by Anwar Hafid in his posts includes background music of contemporary music genres or his unique personal voice, consistent posts every month, and conveying political messages that are in line with his work as a member of the DPR-RI. The three personal branding concepts that are dominant in the post are differentiation, unity, and personality. Each post via a Facebook account shows answers to the three main problems that must be faced in facing the 2024 gubernatorial election, namely having a religious personality, increasing the number of votes in the Provincial DPRD, and campaigning for open politics to eliminate tribal identity politics.